Efektivitas Permainan Tunjuk Abjad Terhadap Pembelajaran Kosakata Bahasa Mandarin di MA Negeri 1 Cilacap - Juwita Aprilianti (Proceedings Series on Social Sciences & Humanities, 2021)
The Point the Alphabet Technique is a vocabulary learning technique by making a word based on the letters it sees in as many numbers as possible. In this research, the Abjad Pointing Technique will be combined with group games. During the game, students will say as many vocabulary as possible according to the alphabet designated by the teacher. The purpose of this study was to determine the effectiveness of the Point Abjad game on learning vocabulary in class X Language MA Negeri 1 Cilacap. This research uses qualitative research. Data collection techniques in this study were interviews, documentation and tests.